The stability and fragility of biological networks: eukaryotic model organism Saccharomyces cerevisiae - Altuntaş, Volkan; Gok, Murat (Ieee, 2017)
Recent studies of biological networks show that these networks arc robust against the random or selective deletion of network nodes and I or edges. Ability to maintain performance of network under mutations is a key feature of live systems that has long been recognized. However, the molecular and cellular basis of this stability has just begun to be understood. Robustness is a key to understanding cellular complexity, illuminating design principles, and encouraging closer interaction between experiment and theory. A biological network mutation can be defined as the creation of a new network with k allowed network change operations for a given G network. While mutating the network, our goal is to observe the change in the measured distance estimate value after k changes of the defined distance measurement method M. In this study, the effects of edge deletion and edge insertion mutations on network topology and diffusion-based function estimation algorithms are investigated by using random mutation model on the protein-protein interaction network of eukaryote Saccharomyces cerevisiae yeast, containing 5936 nodes and 65139 edges. Experimental results shows that Saccharomyces cerevisiae protein-protein interaction network has high robustness against random mutations and that the generated mutations have no significant effect on network topology and estimation techniques.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: biological networks; saccharomyces cerevisiae; network mutations